C3091317 - = I T (By the denition of inverse) = I . So by...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
17. (Statement of the problem.) Proof. A T ( A - 1 ) T = ( A - 1 A ) T (By Algebraic Rule 4 for Transpose) = I T (By the definition of inverse) = I , ( A - 1 ) T A T = ( AA - 1 ) T (By Algebraic Rule 4 for Transpose)
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: = I T (By the denition of inverse) = I . So by the denition, A T is nonsingular and ( A T )-1 = ( A-1 ) T . / 1...
View Full Document

Ask a homework question - tutors are online